In situ generation of carbon dots within a polymer matrix. (3rd February 2020) - Fernandes, D.; Heslop, K.A.; Kelarakis, A.; Krysmann, M.J.; Estevez, L.
Abstract: We disclose a green, cost and time effective approach to impart photoluminescent properties to a range of polymeric materials, an otherwise solvent-intensive and tedious process. Our strategy relies on the thermal treatment of ethanolamine (a carbon and nitrogen-rich precursor) well dispersed within a polymer matrix and gives rise to fluorescent C-dot based nanocomposites, without compromising the physicochemical characteristics of the matrix. The strategy affords at least 20% conversion of the precursor towards fluorescent nanoparticles, eliminates the use of toxic chemicals and is thoroughly compatible with melt processing technologies routinely used in industry. While we focus here on polyethylene (PE), polypropylene (PP) and polyethylene glycol (PEG) nanocomposites, the approach is general and applicable to a variety of thermally stable polymers. The C-dots formed in situ within the PEG matrix have diameters in the range 1–40 nm (as revealed by TEM) and exhibit quantum yield 11% in water compared to 3% for the PE-derived nanoparticles. Graphical abstract: Image 1 Highlights: A cost effective approach to synthesize luminescent polymer nanocomposites is disclosed. The method relies on the in situ pyrolysis of ethanolamine dispersed within a polymer. The method is thoroughly compatible with standard industrial processing (melt mixing). The strategy is general and can be applied to a variety of polymers.